The Impact of the Hamlet Land Pawn Agreement on the Economic Level of Indigenous Peoples in Negeri Piliana, Maluku Tengah Regency - Matuankotta, Jenny K.; Lakburlawal, Mahrita Aprilya; Radjawane, Pieter; Salam, Safrin; Ibrahim, Kayode Muhammed (Fakultas Syariah UIN Sulthan Thaha Saifuddin Jambi, Indonesia, 2023)
This study aims to identify and analyze the hamlet land pawn agreement practice and its impact on the economic level of indigenous peoples in Negeri Piliana, Central Maluku Regency. The method used is sociological juridical research which emphasizes research aimed at obtaining legal knowledge empirically by going directly to the object. The chosen research location was Negeri Piliana, Tehoru District, Central Maluku Regency. The research was conducted using primary and secondary data. The sample selection method used a purposive sampling method. The results of this study indicate that the pawn sales transaction practice in Negeri Piliana, Tehoru District, Central Maluku Regency, has a different concept from the concept according to customary law in general. The pawn sales practice, in this case, is an agreement to give a hamlet (land that has been planted with certain long-lived crops such as coconut, cloves, nutmeg or cocoa) to obtain an amount of money with a mutually agreed repayment period as long as the pawn giver can cover the amount owed along with interest. So that if it is not agreed upon, it can cause the pawn giver as the owner to lose access to the pawned object for an unlimited time, which can impact the economic level of the surrounding community.